Life-cycle assessment of post-disaster temporary housing. Issue 5 (4th July 2017) - Atmaca, Nihat
ABSTRACT: The estimation of energy consumption and related CO2 emissions from buildings is increasingly important in life-cycle assessment (LCA) studies that have been applied in the design of more energy-efficient building construction systems and materials. This study undertakes a life-cycle energy analysis (LCEA) and life-cycle CO2 emissions analysis (LCCO2 A) of two common types of post-disaster temporary houses constructed in Turkey. The proposed model includes building construction, operation and demolition phases to estimate total energy use and CO2 emissions over 15- and 25-year lifespans for container houses (CH) and prefabricated houses (PH) respectively. Energy efficiency and emission parameters are defined per m 2 and on a per capita basis. It is found that the operation phase is dominant in both PH and CH and contributes 86–88% of the primary energy requirements and 95–96% of CO2 emissions. The embodied energy (EE) of the constructions accounts for 12–14% of the overall life-cycle energy consumption. The results show that life-cycle energy and emissions intensity in CH are higher than those for PH. However, this pattern is reversed when energy requirements are expressed on a per capita basis.